Aplicação de um programa de telessaúde por mães para o ensino de reconhecimento de expressões faciais para crianças com transtorno do espectro do autismo - Bondioli, Ricardo Martinelli (Universidade Federal de São Carlos, 2021)
Autistic Spectrum Disorder (ASD) refers to a neurodevelopmental disorder in which limitations to social effects are common, being relevant as processing focused on promoting social behavior in general, including the identification of emotions. With the global Sars-Cov pandemic, telehealth care based on Applied Behavior Analysis (ABA) has been shown to be an alternative, respecting the health protocols suggested to face such a moment. The present study aimed to: 1) evaluate and create conditions for teaching social behaviors for three children with ASD, from the IPO (Operationalized Portage Inventory), in adapted version and a natural situation, and 2) evaluate a teaching procedure using social stories for identification of four facial emotional expressions in subjects with ASD: joy, fear, anger and sadness. Three families with children with ASD were selected, who were assisted in a project with a broader objective in the area of telehealth in ABA. The dependent variables were: pre- and post-test of the child's performance in the IPO-adapted, number of correct responses in the socialization programs, number of correct responses in the emotion faces identification program, score in the interaction checklist and engagement of the intervention videos sent by mothers, score on EVALOF (Scaling Assessment of Oral Language in a Family Context) and measure of social validity of mothers. The independent variable involved the application of the teaching procedure directly by the mothers. The results showed evolution of children (P2 and P3) in skills in the five areas of development, in addition to the acquisition in identifying faces of emotional expressions. Although the three mothers engaged in the intervention, the form and period as it occurred varied among them. Qualitatively, improvements in the skills of mothers in the application of activities were analyzed and they were generally very satisfied with their participation and with the progress of their children. Thus, the proposal for telehealth based on ABA in the area of socialization has promoted the teaching conditions of mothers with their children with ASD in the home environment, during the pandemic period.
Application of a telehealth program by mothers to teach facial expression recognition to children with autism spectrum disorder
Keywords: Análise do comportamento aplicada; Telessáude; Expressão emocional facial; Transtorno do espectro autista; História social; Família; Applied behavior analysis; Telehealth; Emotional facial expression; Autistic spectrum disorder; Social history; Family; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::PROGRAMACAO DE CONDICOES DE ENSINO